Impacts de l’élévation du niveau marin sur l’évolution future d’un marais maritime endigue : le domaine de Graveyron, bassin d’Arcachon (France) - Brice Anselme; Paul Durand; Lydie Goeldner-Gianella; Frédéric Bertrand (VertigO)
The Domaine of Graveyron, located on the Eastern bank of the Arcachon basin, constitutes a marsh with a high ecological and landscape interest. It shelters protected vegetal species like Triglochin barrelieri and is a refuge and breeding place for several birds. It is surrounded by dykes that deteriorate and the marsh frontal part is submerged each high tide. Numerous simulations realised with a digital elevation model show that sea level rise could involve the submersion of the whole Domaine before the end of the century. It could result the substitution of "soft marsh" by a "salted marsh", hence, a biodiversity loss on floristic level. However, it could be possible that sedimentary flows around the Domaine contribute to the reconstitution of the high marsh by sediments accumulation and thus, thwart the submersifs effects of marine level rise.